Properties Characterization of Napier Grass (Pennisetum Purpureum) as the Cost Effective Non-wood Subtitution for Natural Fibre Papermaking - Lim, Hooi Peng (Journal of Advanced Mechanical Engineering Applications, 2020)
Napier grass, scientifically known as pennisetum purpureum is esteemed for its high productivity, robust perennial nature and pest resistance characteristics. This perennial tropical grass has versatile harvesting period and vegetative propagation through stem cutting provide it an excellent fibre reserve. Numerous preliminary studies on properties characterization of napier grass were indicated in the literature, however, a comprehensive and in-depth analysis of using this tropical grass as non-wood substitution for paper is relatively underexplored. Therefore, the primary purpose of this innovation is to explore the potential of using napier grass as the cost effective non-wood substitution for greener paper making. In general, the fibre length of napier grass at approximately 20Âµm which is similar to the short fibre hardwoods, provides an idea of the potential usefulness of these naturally uncultivated crops in pulp and paper making. The resultant lignocellulosic rich non-wood paper are comparable to that of available paper, having lower moisture uptake, better water absorption value, higher tear strength, smoother shear formation and enhanced thermal stability. Additionally, the finer and shorter fibre length of napier grass could intensify the drainage properties and thus reduce the processing costs. Therefore, this new approach demonstrates the feasibility of using napier grass as the non-wood substitute for paper making and it is economically cost effective.